O efeito de real na tevê: marcas do documentário na ficção seriada contemporânea - Gomes, Melissa Maria Fontenele (2018)
This research analyzes the approximations and tensions between that which is real and that which is fiction in contemporary TV shows. Through the concept of real effect, formulated by Roland Barthes (2002), and the concept of style, formulated by David Bordwell (2008) and Jeremy G. Butler (2010), we attempt to perceive how protocols traditionally engendered as a representation of reality, especially those coming from the documentary genre, operate to produce a realistic impression. To do so, this analysis seeks to account four categories shared between the sitcom The Office (NBC: 2005-2013), in which the interview and camera are explored; and the Netflix drama, Narcos (2015-), noticeable for the use of voice over and file image. Moreover, we also highlight other contemporary series in which reality and fiction relate to establish association to the historical world.